Transformation of Antisense Chalcone Synthase (CHS) Gene into Lotus (Nelumbo Nucifera Gaertn.) by Particle Bombardment - Saetiew Kanjana; Ano Prissadang; Parinthawong Nanglak; Arunyanart Sumay (My University, 2017)
Chalcone synthase ( CHS ) is a key enzyme in the flavonoid biosynthesis pathway. CHS genes were cloned from genomic DNA and cDNA from the petals of ' Buntharik ' white lotus and ' Sattabangkacha ' pink lotus by the PCR technique using a specific primer of the CHS gene designed from the GenBank database. Semi-quantitative RT-PCR analysis revealed that the highest CHS gene expression was found in the early budding stage of the pink lotus and was reduced in later stages. Shoot tips from embryos of Buntharik and Rachinee lotus were used to induce shoot clusters by cultivation on a MS medium supplemented with 40 µM NAA and 0.5 µM TDZ for 8 weeks and a MS medium supplemented with 50 µM BA for 8 weeks. An antisense CHS gene (450 bp) from the cDNA of Buntharik lotus was used to construct a plant transformation vector; pCAMBIA1302CHSA. The vector construct was transformed into Buntharik and Rachinee shoot clusters by particle bombardment. After transformant selection and regeneration, two transformants of Buntharik shoot clusters showed GFP green spots and existence of the GFP gene and hpt II gene in the genomic DNA amplified by the PCR technique. In the Rachinee transformants, 3 of 5 showed the GFP green spots and the GFP and hpt II genes were identified in amplification by PCR. After CHS gene expression analyses by semi-quantitative RT-PCR, two transformed Rachinee shoot clusters had a reduction in CHS gene expression.
Keywords: Lotus japonicus; genomic DNA; Plant Gene Expression Analysis